Myeloid cell modulation by tumor-derived extracellular vesicles - Arkhypov, Ihor; Lasser, Samantha; Petrova, Vera; Bitsch, Rebekka; Groth, Christopher; Utikal, Jochen; Altevogt, Peter; Umansky, Viktor (International journal of molecular sciences, 2020)
Extracellular vesicles (EV) can carry proteins, RNA and DNA, thus serving as communication tools between cells. Tumor cells secrete EV, which can be taken up by surrounding cells in the tumor microenvironment as well as by cells in distant organs. Tumor-derived EV (TEV) contain factors induced by tumor-associated hypoxia such as heat shock proteins or a variety of microRNA (miRNA). The interaction of TEV with tumor and host cells can promote cancer angiogenesis, invasion and metastasis. Myeloid cells are widely presented in tissues, comprise the majority of immune cells and play an essential role in immune reactions and tissue remodeling. However, in cancer, the differentiation of myeloid cells and their functions are impaired, resulting in tumor promotion. Such alterations are due to chronic inflammatory conditions associated with cancer and are mediated by the tumor secretome, including TEV. A high capacity of myeloid cells to clear EV from circulation put them in the central position in EV-mediated formation of pre-metastatic niches. The exposure of myeloid cells to TEV could trigger numerous signaling pathways. Progenitors of myeloid cells alter their differentiation upon the contact with TEV, resulting in the generation of myeloid-derived suppressor cells (MDSC), inhibiting anti-tumor function of T and natural killer (NK) cells and promoting thereby tumor progression. Furthermore, TEV can augment MDSC immunosuppressive capacity. Different subsets of mature myeloid cells such as monocytes, macrophages, dendritic cells (DC) and granulocytes take up TEV and acquire a protumorigenic phenotype. However, the delivery of tumor antigens to DC by TEV was shown to enhance their immunostimulatory capacity. The present review will discuss a diverse and complex EV-mediated crosstalk between tumor and myeloid cells in the context of the tumor type, TEV-associated cargo molecules and type of recipient cells.